Certain aspects of theoretical-group approach in problems of nonlinear mechanics - Lopatin , A. K. (Ukrains’kyi Matematychnyi Zhurnal, 1992)
Two aspects of the application of the asymptotic decomposition method to the decomposition and investigation of nonlinear systems are considered. The first one is the extension of the class of functions in terms of which to form the asymptotic decomposition by applying special functions of mathematical physics. The other aspect is the extension of the asymptotic decomposition method to a new class of differential systems, namely, Pfaffian systems in involution.